P113: Comparison of age-adjusted and clinical probability-adjusted D-dimer for diagnosing pulmonary embolism. (15th May 2017) - Sharif, S.; Kearon, C.; Li, M.; Eventov, M.; Jiang, R.; Sneath, P.E.; Leung, R.; de Wit, K.
Abstract : Introduction: Diagnosing pulmonary embolism (PE) in the emergency department can be challenging due to non-specific signs and symptoms; this often results in the over-utilization of CT pulmonary angiography (CT-PA). In 2013, the American College of Chest Physicians identified CT-PA as one of the top five avoidable tests. Age-adjusted D-dimer has been shown to decrease CT utilization rates. Recently, clinical-probability adjusted D-dimer has been promoted as an alternative strategy to reduce CT scanning. The aim of this study is to compare the safety and efficacy of the age-adjusted D-dimer rule and the clinical probability-adjusted D-dimer rule in Canadian ED patients tested for PE.Methods: This was a retrospective chart review of ED patients investigated for PE at two hospitals from April 2013 to March 2015 (24 months). Inclusion criteria were the ED physician ordered CT-PA, Ventilation-Perfusion (VQ) scan or D-dimer for investigation of PE. Patients under the age of 18 were excluded. PE was defined as CT/VQ diagnosis of acute PE or acute PE/DVT in 30-day follow-up. Trained researchers extracted anonymized data. The age-adjusted D-dimer and the clinical probability-adjusted D-dimer rules were applied retrospectively. The rate of CT/VQ imaging and the false negative rates were calculated.Results: In total, 1, 189 patients were tested for PE. 1, 129 patients had a D-dimer test and a Wells score less than 4.0. 364/1, 129 (32.3%, 95%CI 29.6-35.0%) would have undergone imaging for PE if the age-adjusted D-dimer rule was used. 1, 120 patients had a D-dimer test and a Wells score less than 6.0. 217/1, 120 patients (19.4%, 95%CI 17.2-21.2%) would have undergone imaging for PE if the clinical probability-adjusted D-dimer rule was used. The false-negative rate for the age-adjusted D-dimer rule was 0.3% (95%CI 0.1-0.9%). The false-negative rate of the clinical probability-adjusted D-dimer was 1.0% (95%CI 0.5-1.9%).Conclusion: The false-negative rates for both the age-adjusted D-dimer and clinical probability-adjusted D-dimer are low. The clinical probability-adjusted D-dimer results in a 13% absolute reduction in CT scanning compared to age-adjusted D-dimer.